Implementation of model-informed precision dosing for tamoxifen therapy in patients with breast cancer: A prospective intervention study - Ruben Y.M. van Nijnatten; Sanne M. Buijs; Bram C. Agema; Raphaël M.J. Fischer; Inge Ghobadi Moghaddam-Helmantel; Caroline M.E. Contant; Felix E. de Jongh; Auke M.T. Huijben; Manon Kop; Annemieke van der Padt-Pruijsten; Hanneke J.M. Zuetenhorst; Ron H.N. van Schaik; et al. (Breast)
Tamoxifen is an estrogen-receptor (ER) antagonist, used as adjuvant treatment of ER-positive breast cancer. It is converted by CYP2D6 into endoxifen, its most active metabolite. Patients with endoxifen plasma concentrations <16 nM face a higher risk of recurrence. The use of a priori model-informed precision dosing (MIPD) may lead to faster target attainment and thus potentially improve patient outcomes.In total, 106 evaluable patients were prospectively included in this single-arm MIPD-intervention study. Patients received a model-predicted tamoxifen dose when starting tamoxifen-treatment (65.1 % of patients received 20 mg, 16.0 % received 30 mg and 18.9 % received 40 mg). Seventy-five percent of the 40 mg group was predicted to be unable to reach the threshold of 16 nM despite receiving the highest registered dose. After attaining steady-state, 84.0 % of patients reached endoxifen levels ≥16 nM, which was not significantly higher compared to a historical control cohort (77.9 %, p = 0.17). The model showed adequate performance and correctly identified patients requiring 40 mg tamoxifen. Endoxifen samples that were acquired 4–6 weeks after treatment initiation, are informative of steady-state endoxifen levels and can be used to inform MIPD and adjust tamoxifen dosing prior to steady-state attainment.In this first MIPD implementation study for patients treated with tamoxifen, MIPD did lead to more patients achieving endoxifen levels ≥16 nM as compared to the one-dose-fits-all strategy, albeit insignificant. This may partly be explained by a larger proportion of patients who were recommended to switch to an aromatase inhibitor (AI) in the intervention cohort. In conclusion, MIPD seems beneficial compared to one-size-fits-all-dosing, but TDM still remains an important addition.